TASTE OF TRADITION: UNVEILING THE CULINARY TREASURES OF ZAMBIA’S HOSPITALITY SECTOR - Kasonde , Musonda Mwila; Kabwe, Mutale Chanda (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
This study delves into the intricate interplay between food, culture, and the hospitality and tourism industry, focusing on the case of Zambia. Food is not merely sustenance; it serves as a conduit for cultural expression and preservation. The utilization of traditional food in culinary practices has the power to define indigenous identities and attract tourists seeking authentic experiences. However, the globalization and cultural diffusion processes have led to the erosion and hybridization of traditional culinary practices. This research aims to assess the extent to which traditional Zambian food is harnessed within food catering services and its role in fostering the growth of the hospitality and tourism sector. By analyzing the link between food and culture, this study underscores the significance of traditional culinary skills and knowledge that are intricately linked to local geography and cultural heritage. Indigenous communities derive their identities from the food they cultivate, prepare, and consume. Simultaneously, visitors are offered a unique opportunity to engage with foreign cultures through culinary experiences, thereby promoting cross-cultural understanding. The erosion of traditional food practices due to the influx of foreign influences raises concerns about cultural preservation. This research delves into the challenges posed by cultural diffusion, including the risk of losing traditional food utility and the merging of local practices with imported traditions. The Zambian context provides a fertile ground for examining these dynamics, given its rich culinary heritage and the growing hospitality and tourism industry. Through comprehensive empirical analysis, including surveys, interviews, and observations, this study aims to gauge the prevalence of traditional food in Zambian food catering services